(3GdWGbI GdGSJjYGHjI ddGSJKeGQ Hjf GdJbhje h GSJQGJjLjGJ GdJUfjY (B/s - (3bGSe, NGdO eUWais ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI ddfTQ(B, s, 2006)
(3jMJhj GdcJGH Ydi (B: (3GdWGbI GdESJYGHjI ddESJKeGQ aj bWGYG GdUfGYI GdJMhjdjI ,ESJQGJjLjGJ GdJUfjY GdeJHYI aj bWGYGJ GdUfGYI GdJMhjdjI , bjGS GdWGbI GdESJYGHjI ddESJKeGQ aj bWGYGJ GdUfGYI GdJMhjdjI , eYhbGJ GdWGbI GdESJYHjI ddESJKeGQ aj bWGYGJ GdUfGYI GdJMhjdjI(B.s
Keywords: (3GdGSJKeGQs; (3GdUfGYGJ GdJMhjdjIs; (3GdUfGYIs